The potential of biostimulants on soil microbial community: a review - Adedayo, Afeez Adesina; Babalola, Olubukola Oluranti (Frontiers in Industrial Microbiology, 2023)
To improve agricultural sustainability, an agriculturally productive system is required to maintain soil fertility and reduce the loss of soil biodiversity. One of the modern technologies employs microbial biostimulants that create abundant agricultural yield with high nutritional values, controlling disadvantages obtained from environmental changes. This review aimed to provide knowledge on the effects of biostimulants on microbial communities’ potential to promote agricultural production. Plant biostimulants are novel materials applied in the farming sector nowadays to improve crop yield and commonly occur in plant seeds and as an alternative to chemical derivative application on crop plants. Microbial biostimulants function as biological inputs to increase crop production and reduce the decomposition of soil. In conclusion, the application of biostimulants necessitates the accomplishment of an absolute choice of beneficial microbes as well as the potential to combat problems that will be encountered later in the agricultural sector.